PENGARUH ETIKA, PENDIDIKAN DAN PENGALAMAN TERHADAP PROFESIONALISME AUDITOR INTERNAL DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi pada Inspektorat Wilayah Kabupaten Kampar Provinsi Riau) - Arwinda Kurnia; Amir Hasan; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study was aimed to examine the direct effect of Ethics, Education, Experiance and motivation, and also significant effect of Ethics, Education, and Experiance On The Auditor’s Internal Professionalism with motivation as intervening variable. Collecting data of this study using a questionnaire submitted to 43 auditors who work at Inspektorat Jenderal Kampar Regency Riau Province Representation. From questionnaires distributed 43 questionnaires (93%) were completed and can be processed. Data analysis for hypothesis test was done with Partial Least Square (PLS). Parameter Significant tested by comparing the value tstatistic with ttable, where the value tstatistik>ttabel at 0,0=2,02 confidence level, its meaning there significant influence between independent variabel with dependent variabel. Result of this study give evidence that ethics with significant 3,605, education with significant 2,318, experiance with significant 2,311, and motivation with significant 2,733 have effect on Auditor’s internal professionalism. Ethics with significant 6,780 and education with significant 6,896 also have effect on motivation. Ethics with significant 2,512 and also education with significant 2,518 have effect on auditor’s internal professionalism through motivation. But, experiance have no significant effect on motivation and also have no significant on auditor’s internal professionalism through motivation.Keywords: Ethics, Education, Experiance, motivation, and Auditor’s internal professionalism